The phylogeography and incidence of multi-drug resistant typhoid fever in sub-Saharan Africa - Se Eun Park (Nature Portfolio, 2018)
Typhoid fever is caused by the bacterium Salmonella Typhi. Here, Park et al. analyse the genomes of 249 S. Typhi isolates from 11 sub-Saharan African countries, identifying genes and plasmids associated with antibiotic resistance and showing that multi-drug resistance is highly pervasive in sub-Saharan Africa.